RETURN TO SPORT PHYSICAL PERFORMANCE TESTING IN CHILDREN - BUILDING POPULATION NORMS. Issue 3 (31st March 2019) - Myers, Heather; Magill, John; Esposito, Valentine; Messer, Michael; Lentz, Trevor; Riboh, Jonathan
Purpose/Hypothesis: Return to sport (RTS) after anterior cruciate ligament (ACL) reconstruction in children is associated with a much higher risk (˜30%) of subsequent ACL injury than in adults. In adults, delaying RTS until objective physical performance test (PPT) criteria are met reduces re-injury rates. However, normative data on PPTs in children is missing, limiting their utility in this high-risk population. Designing age-specific pediatric guidelines for RTS is therefore a critical area of investigation. Number of Subjects: 63 Materials/Methods: We designed a prospective observational study of 130 healthy pediatric athletes (ages 6 - 18 years, 5 males and 5 females of each age). Each athlete underwent a series of 10 functional tests assessing balance (Y-Balance Test, stork test, stork test on Bosu ball), strength (single leg squat, single leg hop) and composite neuromuscular control (single leg squat on Bosu ball, clockwise and counterclockwise quadrant hop, 6 m timed hop and triple crossover hop). Demographic data including sex, chronologic age, Pubertal Maturity Observational Score (PMOS), height, weight, and body mass index (BMI). Testing order was randomized to reduce confounding from fatigue. Our primary hypothesis was that PPT results would vary predictably with chronologic age. For each PPT, multivariable linear regression was performed including age, sex, PMOS, BMI and testing order as independent variables. Standard "growth curves" for each test were then built based on age and sex. Results: Sixty-three athletes (29 male, 34 female) have completed testing so far (48% enrollment). Mean age was 10.7 +/- 3.2 years (range 6 - 18). Mean PMOS was 3.2 +/- 3.1 (range 0 - 9). PMOS was strongly correlated with chronologic age (Pearson's? = 0.83), therefore PMOS was excluded as a predictor variable in regression models to avoid multicollinearity. Chronologic age was an independent predictor of all PPT results (p < 0.05 in all cases). There was a learning effect for the Bosu Stork test, with athletes doing this test later in the sequence performing better (ß = 2.47, 95% CI 0.74 - 4.19, p = 0.006). Female sex was an independent predictor of a shorter triple crossover hop distance (ß = -74.1, 95% CI -106.9 to -41.2, p < 0.0001). Balance tests showed the least linear relationships with age. The stork test had a clear ceiling effect by age 10 in females and 13 in males. The Bosu Stork test showed wide variability at all ages. Conclusion: Chronologic age is a strong, typically linear predictor of commonly used PPTs in children. The PMOS did not add additional predictive value. Clinical Relevance: The normative data generated in this study help understand normal neuromuscular development, and provide a foundation for creating age-specific RTS scores.